RFID for the supply chain and operations professional - Zelbst, Pamela J.; Sower, Victor E. (Supply and operations management collection., 2021)
The quality and effectiveness of decisions made within an organization and its supply chain depend on the accuracy and timeliness of the information on which they are based. Radio-frequency identification (RFID) is a technology that can provide more accurate information in near realtime and thus increase the quality and timeliness of decisions based on that information. RFID systems are currently in use in areas such as inventory management, process control, asset tracking and monitoring, and retail point of sale. Organizations that appropriately incorporate RFID into their operations and information management systems have increased their agility, effectiveness, and efficiency, resulting in organizational growth and increased profitability.The appropriate utilization of RFID allows organizations to become more agile, resulting in their ability to respond to customers more efficiently and effectively. Technology by itself does not result in improvements, and RFID is no exception. RFID is not a solution for every problem. However, when coupled with other appropriate technologies to address an appropriate objective, RFID can offer a variety of benefits to businesses. The proper integration of RFID into the firm's competitive plans and processes provides the ability to leverage the technology for competitive advantage and results in increased performance for organizations. The intent of this book is to provide a sufficient discussion of RFID to enable readers with no prior knowledge to develop a basic understanding of the technology. The book discusses current applications and specific examples of RFID usage taken from a variety of industries. The appropriate coupling of RFID with other technologies such as global positioning systems (GPS), enterprise resource planning (ERP), and robotics is discussed, as well as an overview of the RFID implementation process. This book helps readers develop an understanding of the capability of the technology to increase an organization's customer responsiveness. In the third edition, the discussion and examples have been updated to reflect the rapid advancement in RFID technology. A new case study and new examples have been added along with updated discussions and projections about RFID technology.